Sodium-supplementing sodium ion battery and preparation method thereof
By preparing nano-scale sodium oxalate composite slurry and performing specific treatments during the electroporation of sodium ion batteries, the problem of low efficiency of sodium ion batteries for the first time is solved, efficient sodium replenishment effect is achieved, and the energy of sodium ion batteries is improved Density and cycle times.
Patent Information
- Application Number
- CN202411307984.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-13
AI Technical Summary
The first-time efficiency of sodium ion batteries is low, mainly because the SEI film needs to be formed during the battery formation process to consume active sodium, which reduces the sodium ion content, resulting in limited energy density. The existing sodium supplementation method has safety risks, high investment or difficulty in realizing The problem.
By preparing sodium oxalate composite slurry, the particle size is 50~200nm, the slurry fineness is ≤5μm, the mass ratio of sodium oxalate to the positive electrode active material is ≤3.6%, and pressure and current are controlled during the electroporation process to reduce sodium oxalate The decomposition voltage makes it suitable for use as a good sodium supplement material.
The decomposition voltage of sodium oxalate is reduced to 3.9~4.0V, which is lower than the maximum operating voltage of sodium ion batteries, and the first efficiency of sodium ion batteries is improved to more than 90%, achieving continuous production in the existing production environment.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a sodium-supplemented sodium ion battery and a preparation method thereof. Background Art
[0002] Sodium-ion batteries do not have the risk of resource shortages, and have the same working principle and manufacturing process as lithium-ion batteries. They can be rapidly developed using the production line of lithium-ion batteries. At present, sodium-ion batteries are already in the industrialization stage, and serve as an effective supplement to lithium-ion batteries in certain specific fields. However, due to the low energy density of sodium-ion batteries, their further large-scale application is limited. Among them, the low initial efficiency of the battery is one of the factors that restrict the energy density of sodium-ion batteries. The low initial efficiency is due to the need to form an SEI film to consume active sodium during battery formation, thereby reducing the sodium ion content. Therefore, in order to solve this problem, the battery needs to be supplemented with sodium to make up for the consumption of sodium.
[0003] The currently used sodium supplementation methods can be roughly divided into the following three categories: Sodium metal flakes / powders are used to coat the surface of the negative electrode or foil when making negative electrode sheets. Since sodium metal is very active, it is very easy to react violently with moisture in the air, posing a safety risk. Therefore, this method requires strict control of the anhydrous nature of the production environment, and even inert gas protection is required when necessary for safe production. This is difficult to achieve in actual production or requires a large investment.
[0004] The electrochemical pre-sodium method first assembles the negative electrode sheet and the pre-sodium electrode sheet into a battery, performs the first cycle formation under the action of an external current to obtain the pre-sodium negative electrode sheet, and then assembles the pre-sodium negative electrode sheet and the required positive electrode sheet into a battery. This method requires an additional step of battery assembly and disassembly process, and also requires ensuring that the disassembled electrode sheet does not come into contact with moisture and oxygen. It is difficult to achieve in the actual production process or requires a large investment.
[0005] Positive electrode sodium supplement additives are required to have suitable decomposition potential, high sodium supplement capacity, stable decomposition products and certain air stability. There are many positive electrode sodium supplement additives reported so far, but due to some problems of each, none of them has been effectively applied.
[0006] Sodium oxalate is used as a sodium supplement additive, with a sodium supplement capacity of nearly 400 mAh / g, which is more than twice that of the current sodium ion battery positive electrode material. And the decomposition product of sodium oxalate is only CO 2 , which can be discharged from the battery after the initial formation. The main problem with sodium oxalate is that its conductivity is very poor, resulting in a decomposition voltage as high as 4.4V, which greatly exceeds the operating voltage range of existing sodium-ion batteries and cannot be used to replenish sodium. Summary of the invention
[0007] In order to overcome the above-mentioned shortcomings, one of the purposes of the present invention is to provide a method for preparing a sodium-supplemented sodium ion battery, reduce the decomposition voltage of sodium oxalate, and enable sodium oxalate to be used as a good sodium-supplementing material in sodium ion batteries.
[0008] In order to achieve the above purpose, the technical solution adopted by the present invention is: a method for preparing a sodium-supplemented sodium ion battery, comprising the following steps: S1. Prepare a sodium oxalate composite slurry, wherein the slurry fineness is ≤5 μm, and the sodium oxalate composite slurry includes sodium oxalate, and the particle size of the sodium oxalate is 50-200 nm; S2, coating the sodium oxalate composite slurry on the positive electrode membrane, wherein the mass ratio of sodium oxalate to the positive electrode active material is ≤3.6%; S3, preparing battery cells and subjecting the battery cells to chemical treatment.
[0009] Exemplarily, the particle size of sodium oxalate is 50nm, 70nm, 90nm, 100nm, 120nm, 140nm, 160nm, 180nm, 200nm or any two thereof; the slurry fineness is 1μm, 2μm, 3μm, 4μm, 5μm or any two thereof. The mass ratio of sodium oxalate to the positive electrode active material is 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6% or any two thereof.
[0010] Further, in step S3, during the formation process of the battery cell, the formation pressure is 0.7-1.2 MPa. Exemplarily, the formation pressure is 0.7 MPa, 0.8 MPa, 0.9 MPa, 1.0 MPa, 1.1 MPa, 1.2 MPa or a range consisting of any two thereof.
[0011] Further, in step S3, during the formation treatment of the battery cell, the formation current is 0.1-0.2 C. Exemplarily, the formation current is 0.1 C, 0.12 C, 0.14 C, 0.15 C, 0.17 C, 0.19 C, 0.2 C or any two thereof.
[0012] Furthermore, in S2, the positive composite electrode coated with the sodium oxalate composite slurry is roll-pressed, and the compaction density of the sodium oxalate composite material is 1.4-1.5 g / cm 3 For example, the compacted density of the sodium oxalate composite material is 1.4 g / cm 3 , 1.42g / cm 3 , 1.44g / cm 3 , 1.46g / cm 3 , 1.48g / cm 3 , 1.50g / cm 3Or a range consisting of any two of them.
[0013] Furthermore, in S1, the sodium oxalate composite slurry includes, by weight, 85-93 parts of sodium oxalate, 5-7 parts of conductive carbon black SP, 2-3 parts of polyvinylidene fluoride PVDF, 0.3-0.7 parts of polyvinylpyrrolidone PVP and 1.2-2.3 parts of carbon nanotubes CNT.
[0014] Illustratively, sodium oxalate is in a range of 85 parts, 86 parts, 87 parts, 88 parts, 89 parts, 90 parts, 91 parts, 92 parts, 93 parts or any two of them; conductive carbon black is in a range of 5.0 parts, 5.5 parts, 6.0 parts, 6.5 parts, 7.0 parts or any two of them; polyvinylidene fluoride is in a range of 2.0 parts, 2.2 parts, 2.5 parts, 2.7 parts, 3.0 parts or any two of them; polyvinyl pyrrolidone is in a range of 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts or any two of them; carbon nanotubes are in a range of 1.2 parts, 1.4 parts, 1.5 parts, 1.7 parts, 2.0 parts, 2.3 parts or any two of them.
[0015] Further, in S1, by weight, the total ratio of sodium oxalate to the conductive agent SP and CNT is 9.4-18.4, and the ratio of SP to CNT is 2.3-4.0. Exemplarily, the total ratio of sodium oxalate to the conductive agent SP and CNT is 9.4, 10, 11, 12, 13, 14, 15, 16, 17, 18, 18.4 or a range consisting of any two thereof; the ratio of SP to CNT is 2.3, 2.5, 3.0, 3.5, 4.0 or a range consisting of any two thereof.
[0016] Furthermore, S1 includes the following steps: S11, put sodium oxalate, SP, PVDF, PVP powder and NMP into a sand mill, add grinding beads with a diameter of 1-1.5 mm, and grind for 30-60 minutes; S12, adding oily CNT conductive slurry into the sand mill, and continuing grinding for 30-60 minutes; S13, transferring the ground slurry to a homogenizer, and treating it under a pressure of 90-110 MPa to obtain a sodium oxalate composite slurry.
[0017] Furthermore, in S3, the specific steps of forming include: S31, charge the battery to 30% SOC; S32, charge to 3.9V at a rate of 0.5C, and let stand for 30 minutes to eliminate the influence of cell polarization; S33, charge to 4.05V with a small constant current of 0.1~0.2C, and then maintain the voltage for 0.5~2h to complete the battery cell formation.
[0018] The present invention also provides a sodium-supplemented sodium ion battery, which is prepared according to the preparation method of the sodium-supplemented sodium ion battery as described above.
[0019] The beneficial effects of the present invention are: 1) Pre-treat the sodium oxalate material to prepare nano-sized sodium oxalate particles, and reduce the decomposition voltage of sodium oxalate to 3.9~4.0V, which is lower than the maximum working voltage of existing sodium ion batteries. Sodium oxalate can be used as a good sodium supplement material in sodium ion batteries, which can increase the initial efficiency of sodium ion batteries from 85% to more than 90%; 2) Preparing the pretreated sodium oxalate and the conductive slurry into a composite slurry, so that the sodium oxalate and the conductive agent are effectively dispersed and fully contacted, thereby reducing the interface impedance; 3) Optimize the battery formation system so that sodium oxalate can be fully decomposed during the formation stage to achieve the effect of sodium supplementation.
[0020] 4) The process and equipment are simple and can be carried out in the existing battery production environment to achieve continuous production. DETAILED DESCRIPTION
[0021] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0022] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.
[0023] The applicant found that sodium oxalate, when used as a sodium supplement additive, has a sodium supplement capacity of nearly 400 mAh / g, which is more than twice that of the current sodium ion battery positive electrode material. In addition, the decomposition product of sodium oxalate is only CO 2 , which can be discharged from the battery after the initial formation. The main problem with sodium oxalate is that its conductivity is very poor, resulting in a decomposition voltage as high as 4.4V, which greatly exceeds the operating voltage range of existing sodium-ion batteries and cannot be used to replenish sodium.
[0024] An embodiment of the present invention provides a method for preparing a sodium-supplemented sodium-ion battery. By improving the method for preparing a sodium-supplemented sodium-ion battery, the decomposition voltage of sodium oxalate can be reduced to 3.9-4.0V, which is lower than the maximum operating voltage of existing sodium-ion batteries. Sodium oxalate can be used as a good sodium-supplemented material in sodium-ion batteries, and the initial efficiency of sodium-ion batteries can be increased from 85% to more than 90%.
[0025] The preparation method specifically comprises the following steps: S1. Preparation of sodium oxalate composite slurry 85-93 parts of sodium oxalate, 5-7 parts of conductive carbon black SP, 2-3 parts of polyvinylidene fluoride PVDF, 0.3-0.7 parts of polyvinyl pyrrolidone PVP and NMP are put into a sand mill, grinding beads with a diameter of 1-1.5 mm are added, and grinding is carried out for 30-60 minutes.
[0026] Add 1.2-2.3 parts of oily carbon nanotube (CNT) conductive slurry into the sand mill and continue grinding for 30-60 minutes.
[0027] Among them, by weight, the ratio of sodium oxalate to the total amount of conductive agent SP and CNT is between 9.4 and 18.4; the ratio of SP to CNT is between 2.3 and 4.0.
[0028] The ground slurry is transferred to a homogenizer and treated at a pressure of 90~110MPa to obtain a dispersed sodium oxalate composite slurry. After pretreatment, a sodium oxalate composite slurry with a particle size of 50~200nm and a slurry fineness of ≤5μm is obtained. By limiting the slurry fineness to ≤5μm and the particle size of sodium oxalate to between 50~200nm, the decomposition voltage of sodium oxalate is reduced, so that the decomposition voltage of sodium oxalate can be reduced to 3.9~4.0V, which is lower than the maximum operating voltage of existing sodium ion batteries. Sodium oxalate can be used as a good sodium supplement material in sodium ion batteries, which can increase the initial efficiency of sodium ion batteries from 85% to more than 90%.
[0029] S2. Preparation of positive composite electrode 1) According to the conventional positive electrode sheet preparation method, the positive electrode slurry is prepared and coated on the aluminum foil. The positive electrode film is obtained after rolling by a roller press.
[0030] 2) Apply the sodium oxalate composite slurry on the positive electrode membrane in a certain proportion, wherein the addition ratio ensures that the mass ratio of the sodium oxalate content to the positive electrode active material is ≤3.6%.
[0031] Because sodium oxalate is used as a sodium supplement, the first coulombic efficiency of the material will increase accordingly as the content of the sodium supplement increases. However, since sodium oxalate releases gas when producing the sodium supplement effect, if the sodium oxalate content is too high, the battery cell will produce too much gas. After the formation is completed, the gas cannot be completely removed and remains in the electrode sheet, causing an increase in side reactions during the charge and discharge process, and ultimately leading to a decrease in cycle life. At the same time, the first efficiency of the battery cell is not only related to the negative electrode material, but also to the first efficiency of the positive electrode material. The effect of the sodium supplement can only make up for the impact of the negative electrode, and cannot compensate for the active sodium lost due to the positive electrode material. Therefore, excessive addition of sodium supplements cannot infinitely improve the first efficiency of the battery cell. The present invention has shown through research that the mass ratio of sodium oxalate content to positive electrode active material is ≤3.6%, preferably 3.6%, and the first efficiency and number of cycles of the battery are optimal.
[0032] The positive electrode composite electrode coated with sodium oxalate composite slurry is rolled to the designed thickness under a certain pressure to form the final positive electrode sheet. The compaction density of the sodium oxalate composite material is kept between 1.4 and 1.5 g / cm 3 between.
[0033] S3, preparing battery cells and subjecting the battery cells to chemical treatment.
[0034] 1) The positive electrode, separator and negative electrode are stacked on the stacking machine according to the design, and then the required battery cell is obtained after the processes of ear welding, shelling, drying, liquid injection and sealing.
[0035] 2) Transfer the battery cells to the forming equipment and perform pressurized forming under specific pressure and forming steps.
[0036] During the formation process, the battery cell is always kept under a pressure of 0.7~1.2MPa to ensure that the electrodes are tightly fitted, the sodium oxalate can be fully reacted, and the gas produced by the decomposition of the sodium oxalate can be discharged in time.
[0037] After the formation begins, the battery is charged to 30% SOC using a conventional formation system, then charged to 3.9V at a rate of 0.5C, and left to stand for 30 minutes to eliminate the influence of cell polarization. Then, it is charged to 4.05V at a small constant current of 0.1~0.2C to complete the decomposition of the sodium oxalate material; then the pressure is maintained for 0.5~2h to ensure that the generated gas is completely removed and the cell formation is completed.
[0038] 3) After formation, the air bag is removed and secondary sealing is performed, and the sodium-supplemented sodium ion battery is obtained after volume separation.
[0039] Example The following examples describe the disclosure of the present invention in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present invention will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0040] Example 1 A method for preparing a sodium-supplemented sodium ion battery comprises the following steps: S1. Preparation of sodium oxalate composite slurry 90 parts of sodium oxalate, 5.3 parts of conductive carbon black SP, 2.5 parts of polyvinylidene fluoride PVDF, 0.5 parts of polyvinyl pyrrolidone PVP and NMP were put into a sand mill, and grinding beads with a diameter of 1 mm were added, and the mixture was ground for 45 minutes.
[0041] Add 1.7 parts of oily carbon nanotube (CNT) conductive slurry into the sand mill and continue grinding for 45 minutes.
[0042] The ratio of sodium oxalate to the total amount of conductive agent SP and CNT is 12.9; the ratio of SP to CNT is 3.1.
[0043] The ground slurry was transferred to a homogenizer and treated under a pressure of 100 MPa to obtain a dispersed sodium oxalate composite slurry. After pretreatment, a sodium oxalate composite slurry with a particle size of 80 nm and a slurry fineness of 4 μm was obtained.
[0044] S2. Preparation of positive composite electrode 1) According to the conventional positive electrode sheet preparation method, the positive electrode slurry is prepared and coated on the aluminum foil. The positive electrode film is obtained after rolling by a roller press.
[0045] 2) The sodium oxalate composite slurry is coated on the positive electrode membrane in a certain proportion, and the addition proportion of the sodium oxalate composite slurry ensures that the ratio of sodium oxalate content to positive electrode active material is 3.6%.
[0046] The coated positive electrode composite electrode is rolled to the designed thickness under a certain pressure to form the final positive electrode sheet. The compaction density of the sodium oxalate composite material is maintained at 1.43 g / cm 3 .
[0047] S3, preparing battery cells and subjecting the battery cells to chemical treatment.
[0048] 1) The positive electrode, separator and negative electrode are stacked on the stacking machine according to the design, and then the required battery cell is obtained after the processes of ear welding, shelling, drying, liquid injection and sealing.
[0049] 2) Transfer the battery cells to the forming equipment and perform pressurized forming under specific pressure and forming steps.
[0050] During the formation process, the battery cell is always kept under a pressure of 1.0MPa to ensure that the electrodes are tightly fitted, the sodium oxalate can be fully reacted, and the gas produced by the decomposition of the sodium oxalate can be discharged in time.
[0051] After the formation begins, the battery is charged to 30% SOC using a conventional formation system, then charged to 3.9V at a rate of 0.5C, and left to stand for 30 minutes to eliminate the influence of cell polarization. Then, it is charged to 4.05V at a small constant current of 0.1C to complete the decomposition of the sodium oxalate material; then the pressure is maintained for 1 hour to ensure that the generated gas is completely removed and the cell formation is completed.
[0052] 3) After formation, the air bag is removed and secondary sealing is performed, and the sodium-supplemented sodium ion battery is obtained after volume separation.
[0053] Example 2 Example 2 is basically the same as Example 1, with the main differences being: the sodium oxalate composite slurry components, the sodium oxalate particle size, and the fineness of the sodium oxalate slurry. Specifically: S1. Preparation of sodium oxalate composite slurry 87.3 parts of sodium oxalate, 6.9 parts of conductive carbon black SP, 2.8 parts of polyvinylidene fluoride PVDF, 0.7 parts of polyvinylpyrrolidone PVP and NMP were put into a sand mill, and grinding beads with a diameter of 1 mm were added, and the mixture was ground for 45 minutes.
[0054] Add 2.3 parts of oily carbon nanotube (CNT) conductive slurry into the sand mill and continue grinding for 45 minutes.
[0055] The ratio of sodium oxalate to the total amount of conductive agent SP and CNT is 9.5; the ratio of SP to CNT is 3.0.
[0056] The ground slurry was transferred to a homogenizer and treated under a pressure of 100 MPa to obtain a dispersed sodium oxalate composite slurry. After pretreatment, a sodium oxalate composite slurry with a particle size of 82 nm and a slurry fineness of 5 μm was obtained.
[0057] Example 3 Example 3 is basically the same as Example 1, with the main differences being: the sodium oxalate composite slurry components, the sodium oxalate particle size, and the fineness of the sodium oxalate slurry. Specifically: S1. Preparation of sodium oxalate composite slurry 92.6 parts of sodium oxalate, 3.9 parts of conductive carbon black SP, 2 parts of polyvinylidene fluoride PVDF, 0.3 parts of polyvinyl pyrrolidone PVP and NMP were put into a sand mill, and grinding beads with a diameter of 1 mm were added, and the mixture was ground for 45 minutes.
[0058] Add 1.2 parts of oily carbon nanotube (CNT) conductive slurry into the sand mill and continue grinding for 45 minutes.
[0059] The ratio of sodium oxalate to the total amount of conductive agent SP and CNT is 18.2; the ratio of SP to CNT is 3.3.
[0060] The ground slurry was transferred to a homogenizer and treated under a pressure of 100 MPa to obtain a dispersed sodium oxalate composite slurry. After pretreatment, a sodium oxalate composite slurry with a particle size of 85 nm and a slurry fineness of 3 μm was obtained.
[0061] Example 4 Example 4 is basically the same as Example 1, with the main differences being: the sodium oxalate composite slurry components, the sodium oxalate particle size, and the fineness of the sodium oxalate slurry. Specifically: S1. Preparation of sodium oxalate composite slurry 90 parts of sodium oxalate, 5 parts of conductive carbon black SP, 2.5 parts of polyvinylidene fluoride PVDF, 0.4 parts of polyvinyl pyrrolidone PVP and NMP were put into a sand mill, and grinding beads with a diameter of 1 mm were added, and the mixture was ground for 45 minutes.
[0062] Add 2.1 parts of oily carbon nanotube (CNT) conductive slurry into the sand mill and continue grinding for 45 minutes.
[0063] The ratio of sodium oxalate to the total amount of conductive agent SP and CNT is 12.7; the ratio of SP to CNT is 2.4.
[0064] The ground slurry was transferred to a homogenizer and treated under a pressure of 100 MPa to obtain a dispersed sodium oxalate composite slurry. After pretreatment, a sodium oxalate composite slurry with a particle size of 80 nm and a slurry fineness of 4 μm was obtained.
[0065] Example 5 Example 5 is basically the same as Example 1, with the main differences being: the sodium oxalate composite slurry components, the sodium oxalate particle size, and the fineness of the sodium oxalate slurry. Specifically: S1. Preparation of sodium oxalate composite slurry 90 parts of sodium oxalate, 5.6 parts of conductive carbon black SP, 2.5 parts of polyvinylidene fluoride PVDF, 0.5 parts of polyvinyl pyrrolidone PVP and NMP were put into a sand mill, and grinding beads with a diameter of 1 mm were added, and the mixture was ground for 45 minutes.
[0066] Add 1.4 parts of oily carbon nanotube (CNT) conductive slurry into the sand mill and continue grinding for 45 minutes.
[0067] The ratio of sodium oxalate to the total amount of conductive agent SP and CNT is 12.9; the ratio of SP to CNT is 4.0.
[0068] The ground slurry was transferred to a homogenizer and treated under a pressure of 100 MPa to obtain a dispersed sodium oxalate composite slurry. After pretreatment, a sodium oxalate composite slurry with a particle size of 76 nm and a slurry fineness of 4 μm was obtained.
[0069] Example 6 Example 6 is basically the same as Example 1, with the main difference being that in step S2, during the process of preparing the positive composite electrode, the ratio of the sodium oxalate content to the positive electrode active material is 3.0%.
[0070] Example 7 Example 7 is basically the same as Example 1, with the main difference being that during the cell formation process in step S3, the cell is always kept under a pressure of 1.2 MPa during the formation process.
[0071] Example 8 Example 8 is basically the same as Example 1, with the main difference being that during the cell formation process in step S3, the cell is always kept under a pressure of 0.7 MPa during the formation process.
[0072] Example 9 Example 9 is basically the same as Example 1, with the main difference being that during the preparation of the S2 positive composite electrode, the compaction density of the sodium oxalate composite material is 1.50 g / cm 3 .
[0073] Example 10 Example 10 is basically the same as Example 1, with the main difference being that during the preparation of the S2 positive composite electrode, the compaction density of the sodium oxalate composite material is 1.40 g / cm 3 .
[0074] Embodiment 11 Example 11 is basically the same as Example 1, with the main difference being that during the cell formation process in step S3, the formation current is 0.2C. The specific steps are as follows: after the formation begins, the conventional formation system is used to charge to 30% SOC, and then charged to 3.9V at a rate of 0.5C, and allowed to stand for 30 minutes to eliminate the influence of cell polarization. Then, a small current constant current of 0.2C is used to charge to 4.05V to complete the decomposition of the sodium oxalate material; then the pressure is maintained for 1 hour to ensure that the generated gas is completely removed to complete the cell formation.
[0075] Comparative Example 1 Comparative Example 1 is basically the same as Example 1, with the main difference being that the sodium oxalate particle size and the fineness of the sodium oxalate slurry in the sodium oxalate composite slurry are different. Specifically, the sodium oxalate composite slurry with a particle size of 300 nm and a slurry fineness of 5 μm is obtained.
[0076] Comparative Example 2 Comparative Example 1 is basically the same as Example 1, with the main difference being that the sodium oxalate particle size and the fineness of the sodium oxalate slurry in the sodium oxalate composite slurry are different. Specifically, the sodium oxalate composite slurry with a particle size of 82 nm and a slurry fineness of 8 μm is obtained.
[0077] Comparative Example 3 Comparative Example 3 is basically the same as Example 1, with the main differences being: the sodium oxalate composite slurry components, the sodium oxalate particle size, and the sodium oxalate slurry fineness. Specifically: S1. Preparation of sodium oxalate composite slurry 93.5 parts of sodium oxalate, 3.2 parts of conductive carbon black SP, 2.0 parts of polyvinylidene fluoride PVDF, 0.3 parts of polyvinyl pyrrolidone PVP and NMP were put into a sand mill, and grinding beads with a diameter of 1 mm were added, and the mixture was ground for 45 minutes.
[0078] Add 1.0 part of oily carbon nanotube (CNT) conductive slurry into the sand mill and continue grinding for 45 minutes.
[0079] The ratio of sodium oxalate to the total amount of conductive agent SP and CNT is 22.3; the ratio of SP to CNT is 3.2.
[0080] The ground slurry was transferred to a homogenizer and treated under a pressure of 100 MPa to obtain a dispersed sodium oxalate composite slurry. After pretreatment, a sodium oxalate composite slurry with a particle size of 125 nm and a slurry fineness of 5 μm was obtained.
[0081] Comparative Example 4 Comparative Example 4 is basically the same as Example 1, with the main differences being: the sodium oxalate composite slurry components, the sodium oxalate particle size, and the sodium oxalate slurry fineness. Specifically: S1. Preparation of sodium oxalate composite slurry 90 parts of sodium oxalate, 4.5 parts of conductive carbon black SP, 2.5 parts of polyvinylidene fluoride PVDF, 0.5 parts of polyvinyl pyrrolidone PVP and NMP were put into a sand mill, and grinding beads with a diameter of 1 mm were added, and the mixture was ground for 45 minutes.
[0082] Add 2.5 parts of oily carbon nanotube (CNT) conductive slurry into the sand mill and continue grinding for 45 minutes.
[0083] The ratio of sodium oxalate to the total amount of conductive agent SP and CNT is 12.9; the ratio of SP to CNT is 1.8.
[0084] The ground slurry was transferred to a homogenizer and treated under a pressure of 100 MPa to obtain a dispersed sodium oxalate composite slurry. After pretreatment, a sodium oxalate composite slurry with a particle size of 100 nm and a slurry fineness of 4 μm was obtained.
[0085] Comparative Example 5 Comparative Example 5 is substantially the same as Example 1, with the main difference being that in step S2, during the process of preparing the positive composite electrode, the ratio of the sodium oxalate content to the positive electrode active material is 3.8%.
[0086] Comparative Example 6 Comparative Example 6 is basically the same as Example 1, with the main difference that during the preparation of the S2 positive composite electrode, the compaction density of the sodium oxalate composite material is 1.60 g / cm 3 .
[0087] Comparative Example 7 Comparative Example 7 is basically the same as Example 1, with the main difference that during the preparation of the S2 positive composite electrode, the compaction density of the sodium oxalate composite material is 1.30 g / cm 3 .
[0088] Comparative Example 8 Comparative Example 8 is basically the same as Example 1, with the main difference being that during the cell formation process in step S3, the formation pressure is 0.
[0089] Comparative Example 9 Comparative Example 9 is basically the same as Example 1, with the main difference being that during the cell formation process in step S3, the formation pressure during the formation process is 1.5 MPa.
[0090] Comparative Example 10 Comparative Example 10 is basically the same as Example 1, with the main difference being that during the cell formation process in step S3, the formation current is 0.33C. The specific steps are as follows: after the formation begins, the conventional formation system is used to charge to 30% SOC, and then charged to 3.9V at a rate of 0.5C, and allowed to stand for 30 minutes to eliminate the influence of cell polarization. Then, a small current constant current of 0.33C is used to charge to 4.05V to complete the decomposition of the sodium oxalate material; then the pressure is maintained for 1 hour to ensure that the generated gas is completely removed to complete the cell formation.
[0091] Comparative Example 11 Comparative Example 11 is basically the same as Example 1, with the main difference that during the cell formation process in step S3, the formation current is 0.05C. The specific steps are as follows: after the formation begins, the conventional formation system is used to charge to 30% SOC, and then charged to 3.9V at a rate of 0.5C, and allowed to stand for 30 minutes to eliminate the influence of cell polarization. Then, a small current constant current of 0.05C is used to charge to 4.05V to complete the decomposition of the sodium oxalate material; then the pressure is maintained for 1 hour to ensure that the generated gas is completely removed to complete the cell formation.
[0092] Experimental Examples The performance of the batteries prepared in Examples 1-11 and Comparative Examples 1-11 was tested. The test results are shown in Table 1. 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 Materials, the negative electrode material is made of hard carbon material, and the electrolyte is NaPF 6 The electrolyte is a commercial electrolyte with PC, EMC, DEC, FEC, PS, etc. as solvents. The compacted density of the positive electrode is 3.2g / cm 3 The compaction density of the negative electrode is 1.0g / cm 3 .
[0093] The first efficiency η of the battery cell: the charging capacity during formation is recorded as Q1; the first charging capacity during capacity division is Q2; the first discharging capacity during capacity division is Q3. The first efficiency η=Q3 / (Q1+Q2)*100%.
[0094] Battery cell cycle life: After the battery cell has completed capacity division, charge and discharge cycles are performed at a current of 1C / 1C. The cycle is terminated when the discharge capacity retention rate of the battery cell is lower than 80% of the capacity of the first cycle, and the number of battery cell cycles is recorded.
[0095] Table 1
[0096] The first efficiency of the battery prepared in Examples 1-11 reached more than 91.7%, and the number of cycles reached 1150 times and above. Among them, the battery prepared in Example 1 had the best effect, with an initial efficiency of 93.3% and a number of cycles of 1300 times. The present invention improves the preparation method of sodium-supplemented sodium-ion batteries, so that the decomposition voltage of sodium oxalate can be reduced to 3.9~4.0V, which is lower than the maximum operating voltage of existing sodium-ion batteries. Sodium oxalate can be used as a good sodium-supplementing material in sodium-ion batteries, and the first efficiency of sodium-ion batteries can be increased from 85% to more than 91%.
[0097] Compared with Example 1, the particle size of sodium oxalate in Comparative Example 1 is increased to 300 nm. The particle size of sodium oxalate is too large, and its decomposition pressure is relatively large, which is not conducive to sodium oxalate providing a high capacity of sodium ions, causing the battery's initial efficiency and cycle number to decrease. Specifically, the battery's initial efficiency is reduced to less than 90%, and the cycle number is reduced to less than 1000.
[0098] Compared with Example 1, in Comparative Example 2, the fineness of the sodium oxalate slurry is increased to 8 μm, resulting in a decrease in the initial efficiency and the number of cycles of the battery. Specifically, the initial efficiency of the battery is reduced to less than 90%, and the number of cycles is reduced to less than 1000.
[0099] Compared with Example 1, in Comparative Example 3, the amount of sodium oxalate added is increased, and the ratio of the amount of sodium oxalate added to the total amount of conductive agent SP and CNT is 22.3, which exceeds the range of 9.4-18.4, and the first efficiency and cycle number of the battery are reduced, specifically, the first efficiency of the battery is reduced to less than 90%, and the cycle number is reduced to less than 1000. Therefore, according to the experimental data of Examples 1-5 and Comparative Example 3, it can be seen that the ratio of the amount of sodium oxalate added to the total amount of conductive agent SP and CNT is in the range of 9.4-18.4, and the first efficiency and cycle number of the battery are optimal.
[0100] Compared with Example 1, the ratio of SP to CNT in Comparative Example 4 is reduced to only 1.8, and the first efficiency and cycle number of the battery are reduced. Therefore, according to the experimental data of Examples 1-5 and Comparative Example 4, it can be seen that the ratio of the conductive agent SP to CNT is in the range of 2.3~4.0, and the first efficiency and cycle number of the battery are optimal.
[0101] Compared with Example 1, in Comparative Example 5, the ratio of sodium oxalate content to positive electrode active material increases to 3.8%. Although the initial efficiency of the battery is not greatly affected, the number of cycles is reduced. Therefore, according to the experimental data of Example 1, Example 6 and Comparative Example 5, it can be seen that in the process of preparing the positive composite electrode in step S2, the ratio of sodium oxalate content to positive electrode active material is not greater than 3.6%, and the initial efficiency and cycle number of the battery are optimal.
[0102] According to the experimental data of Example 1, Example 9, Example 10, Comparative Example 6 and Comparative Example 7, the compaction density of the sodium oxalate composite material is 1.4-1.5 g / cm 3 Within this range, the battery's initial efficiency and cycle number are optimal.
[0103] According to the experimental data of Example 1, Example 7, Example 8 and Comparative Example 8, Comparative Example 9, when the battery cell is always subjected to a pressure of 0.7-1.2 MPa during the formation process, the initial efficiency and the number of cycles of the battery are optimal.
[0104] According to the experimental data of Example 1, Example 11 and Comparative Examples 10 and 11, charging to 4.05V with a small constant current between 0.1 and 0.2C can promote the decomposition of the sodium oxalate material, and the initial efficiency and cycle number of the battery are optimal.
[0105] The present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, change of structural morphology, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0106] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0107] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0108] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
[0109] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a sodium-supplemented sodium-ion battery, comprising the following steps: S1. Prepare a sodium oxalate composite slurry, wherein the slurry fineness is ≤5 μm, and the sodium oxalate composite slurry includes sodium oxalate, and the particle size of the sodium oxalate is 50-200 nm; S2, coating the sodium oxalate composite slurry on the positive electrode membrane, wherein the mass ratio of sodium oxalate to the positive electrode active material is ≤3.6%; S3, preparing battery cells and subjecting the battery cells to chemical treatment.
2. The method for preparing a sodium-supplemented sodium ion battery according to claim 1, It is characterized in that In step S3, during the formation process of the battery cell, the formation pressure is 0.7-1.2 MPa.
3. The method for preparing a sodium-supplemented sodium ion battery according to claim 1, It is characterized in that In step S3, during the formation process of the battery cell, the formation current is 0.1-0.2C.
4. The method for preparing a sodium-supplemented sodium ion battery according to claim 1, It is characterized in that S2 also includes rolling the positive composite electrode coated with the sodium oxalate composite slurry, and the compaction density of the sodium oxalate composite material is 1.4-1.5 g / cm 3 .
5. The method for preparing a sodium-supplemented sodium ion battery according to claim 1, It is characterized in that In S1, the sodium oxalate composite slurry comprises 85 to 93 parts by weight of sodium oxalate Na 2 C 2 O 4 , 5~7 parts of conductive carbon black SP, 2~3 parts of polyvinylidene fluoride PVDF, 0.3~0.7 parts of polyvinyl pyrrolidone PVP and 1.2~2.3 parts of carbon nanotubes CNT.
6. The method for preparing a sodium-supplemented sodium ion battery according to claim 5, It is characterized in that By weight, sodium oxalate 2 C 2 O 4 The total ratio of conductive agent SP and CNT is 9.4~18.4, and the ratio of SP to CNT is 2.3~4.
0.
7. The method for preparing a sodium-supplemented sodium ion battery according to claim 1, It is characterized in that S1 includes the following steps: S11, sodium oxalate Na 2 C 2 O 4 , conductive carbon black SP, polyvinylidene fluoride PVDF, polyvinyl pyrrolidone PVP powder and N-methyl pyrrolidone NMP are put into a sand mill, grinding beads with a diameter of 1-1.5 mm are added, and grinding is carried out for 30-60 minutes; S12, adding oily CNT conductive slurry into the sand mill, and continuing grinding for 30-60 minutes; S13, transferring the ground slurry to a homogenizer, and treating it under a pressure of 90-110 MPa to obtain a sodium oxalate composite slurry.
8. The method for preparing a sodium-supplemented sodium ion battery according to claim 1, It is characterized in that In S3, the specific steps of formation include: S31, charge the battery to 30% SOC; S32, charge to 3.9V at a rate of 0.5C, and let stand for 30 minutes to eliminate the influence of cell polarization; S33, charge to 4.05V with a small constant current of 0.1~0.2C to complete the battery cell formation.
9. The method for preparing a sodium-supplemented sodium ion battery according to claim 1, It is characterized in that In S33, charge to 4.05 V and then maintain the voltage for 0.5 to 2 hours.
10. A sodium-supplemented sodium-ion battery, prepared according to the method for preparing a sodium-supplemented sodium-ion battery according to claims 1-9.
